MENUMBUHKAN JIWA KEWIRAUSAHAAN UNTUK BERSAING DI ERA INDUSTRI 5.0 DI KELURAHAN PRINGREJO PEKALONGAN - Meliza Meliza (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2023)
The younger generation plays an important role in increasing the quantity and quality of entrepreneurs in Indonesia. However, the majority of young generation do not have a formidable entrepreneurial spirit to be able to face business challenges in the future. As a result, many young entrepreneurs in Indonesia experience failure in entrepreneurship. They are unable to sustain their businesses in the long term. Therefore, socialization activities about the importance of fostering an entrepreneurial spirit in the younger generation are very much needed. Community Service Activities (PkM) in the form of socialization are carried out in Pringrejo Village, Pekalongan District. This activity was attended by Karang Taruna of Pringrejo village. The activity phase includes identification, socialization, and evaluation. The identification results at the initial stage showed that the majority of participants did not own a business. While the majority of participants who already have a business to pursue business in the culinary field. At the evaluation stage, there was an increase in the number of participants who understood the importance of an entrepreneurial spirit from 24% of the total participants at the time before the socialization was carried out to 84% after the socialization was carried out.